Analyzing three pedigrees in X-linked Alport syndrome with the presentation of nephrotic syndrome - Zhang, Jian-Hui; Liu, Jie; Ruan, Dan-Dan; Chen, Qian; Yang, Jie; Wu, Min; Yu, Hong-Ping; Liao, Li-Sheng; Zheng, Xiao-Ling; Luo, Jie-Wei; Zhang, Li (Frontiers in Genetics, 2024)
Background: Alport syndrome (AS) is a common cause of end-stage renal disease (ESRD) with various clinical symptoms and incomplete manifestation. Patients with AS and other renal disorders are often misdiagnosed. This study reported three X-linked dominant Alport syndrome (XLAS) pedigrees with nephrotic syndrome (NS) as the predominant phenotype and analyzed COL4A5 gene alterations. Methods: Three Han Chinese XLAS pedigrees were recruited and clinical phenotypes were obtained. The pre-certified individuals' peripheral blood DNA was taken and whole genome Next-generation sequencing (NGS) was performed for candidate gene and mutation screening, followed by NGS or Sanger sequencing of suspected mutant types in participating family members. Results: Both probands A and B were diagnosed with NS by biochemical tests and Xlinked Alport syndrome-associated renal injury by renal biopsy. The biopsy revealed focal foamy cells in the renal interstitial, tearing and delamination changes in the glomerular basement membrane, and negative α3 and α5 chains of type IV collagen. Proband C, who was earlier diagnosed with NS, has now advanced to ESRD, along with his mother and Proband A's mother. Genetic sequencing of all three pedigrees identified three mutations c.5020C>T, c.4435_4445del, and c.1584_1587+6del in the X-linked dominant gene COL4A5 (NM_000495.5). These mutations lead to the production of shortened proteins, potentially impacting the function of COL4A5 and causing pathogenic effects. Conclusion: The novel c.4435_4445del and c.1584_1587+6del mutations not only enriched the spectrum of mutations in the COL4A5 gene but also carriers of both mutation sites and mutation c.5020C>T can have NS as their primary clinical manifestation.